Scholar Plot: Design and Evaluation of an Information Interface for Faculty Research Performance - Majeti, Dinesh; Akleman, Ergun; Ahmed, Mohammed Emtiaz; Petersen, Alexander M.; Uzzi, Brian; Pavlidis, Ioannis (Frontiers in Research Metrics and Analytics, 2020)
The ability to objectively assess academic performance is critical to rewarding academic merit, charting academic policy, and promoting science. Quintessential to performing these functions is first the ability to collect valid and current data through increasingly automated online interfaces. Moreover, it is crucial to remove disciplinary and other biases from these data, presenting them in ways that support insightful analysis at various levels. Existing systems are lacking in some of these respects. Here we present Scholar Plot (SP), an interface that harvests bibliographic and research funding data from online sources. SP addresses systematic biases in the collected data through nominal and normalized metrics. Eventually, SP combines synergistically these metrics in a plot form for expert appraisal, and an iconic form for broader consumption. SP’s plot and iconic forms are scalable, representing equally well individual scholars and their academic units, thus contributing to consistent ranking practices across the university organizational structure. In order to appreciate the design principles underlying SP, in particular the informativeness of nominal versus normalized metrics, we also present the results of an evaluation survey taken by senior faculty (n=28) with significant promotion and tenure assessment experience.